Hunting the Pertinency of Bloom Filter in Computer Networking and Beyond: A Survey. (5th February 2019) - Patgiri, Ripon; Nayak, Sabuzima; Borgohain, Samir Kumar
Abstract : Bloom filter is a probabilistic data structure to filter a membership of a set. Bloom filter returns "true" or "false" with an error tolerance depending on the presence of the element in the set. Bloom filter is used to boost up the performance of a system using small space overhead. It is extensively used since its inception. The Bloom filter has met wide area of applications. Bloom filter is used in entire computing field irrespective of application and research domain. Bloom filter poses (i) high adaptability, (ii) low memory space overhead as compared to hashing algorithms, (iii) high scalability, and (iv) high performance. In this article, we uncover the application area of Bloom filter in computer networking and its related domain.